2011
DOI: 10.3109/01902148.2010.538132
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of monocyte/macrophage- selective markers in human idiopathic pulmonary fibrosis

Abstract: Idiopathic interstitial pneumonias are a group of idiopathic interstitial lung diseases of which idiopathic pulmonary fibrosis (IPF) is the lesion of usual interstitial pneumonia. Although the pathogenic mechanisms remain incompletely understood, disease-specific changes in blood, a readily accessible biospecimen, have not been fully characterized. To identify biomarkers from blood and sera, the immune status of IPF patients and control subjects without structural lung disease was quantified by measuring cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
(82 reference statements)
1
32
0
Order By: Relevance
“…SPP1 (OPN) has been reported to be induced and to function during wound healing and fibrosis in multiple tissues and organs including the skin, liver, and heart (Leung et al 2013; Matsui et al 2004; Mori et al 2008). The SPP1 level was increased in peripheral blood mononuclear cells and the bronchoalveolar lavage fluid from IPF patients (Desai et al 2011; Pardo et al 2005), as well as mouse lungs exposed to bleomycin (Berman et al 2004). We found that the transcription level of Spp1 was induced by bleomycin or paraquat for more than tenfold; the Spp1 level was also increased by silica for 3.839-fold, though the p value with FDR of silica-treated group was higher than 0.05 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SPP1 (OPN) has been reported to be induced and to function during wound healing and fibrosis in multiple tissues and organs including the skin, liver, and heart (Leung et al 2013; Matsui et al 2004; Mori et al 2008). The SPP1 level was increased in peripheral blood mononuclear cells and the bronchoalveolar lavage fluid from IPF patients (Desai et al 2011; Pardo et al 2005), as well as mouse lungs exposed to bleomycin (Berman et al 2004). We found that the transcription level of Spp1 was induced by bleomycin or paraquat for more than tenfold; the Spp1 level was also increased by silica for 3.839-fold, though the p value with FDR of silica-treated group was higher than 0.05 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1(a), leukocytes accumulated in response to 50 and 100 ng/cavity eotaxin, in amounts that were significantly different from the RPMI controls (0 ng/cavity) as well as from lower doses of eotaxin (10 and 25 ng/cavity). These leukocytes included variable numbers of eosinophils (Figure 1(b)), monocytes/macrophages [39, 40] (Figure 1(c)), and neutrophils (Figure 1(d)). The morphology of all three leukocyte populations was recognizable without ambiguity, as shown in a representative photomicrograph (supplementary Figure 1 available online at http://dx.doi.org/10.1155/2014/102160).…”
Section: Resultsmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease characterized by fibroblast proliferation and extracellular remodeling 2,3. Common to both diseases is the highly altered interaction between fibrogenesis and fibrolysis leading to functional impairment of the lungs.…”
Section: Introductionmentioning
confidence: 99%